Cinematic Culture During the War in Ukraine: Surviving the Year of Brutalities - Shumylovych, Bohdan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
Russia’s war against Ukraine has brought a humanitarian catastrophe to Europe and disrupted previously established cultural practices and rituals. One such practice has been the making and watching of films, constituting a further blow to the Ukrainian film industry, which has already experienced modifications caused by the VoD (video-on-demand) business mode and the coronavirus crisis. This study intends to highlight how the culture of cinema changed in the cities of Ukraine in 2022 that suffered and are still suffering from shelling and fighting. Its findings are based on ethnographic observations, oral history, and secondary research of public data.